La Educación Como Determinante Del Crecimiento Económico De México, 1990-2014 - Favila-Tello, Antonio (European Scientific Journal, ESJ, 2018)
This paper seeks to test two hypotheses: the first one indicates that education was a determining factor of the economic growth of Mexico during the period 1990-2014. The second one seeks to prove the strength of this relationship through a regression model by Ordinary Least Squares where Mexican economic growth is determined by education, gross capital formation, exports, Foreign Direct Investment, industry value added, the birth rate, and the technological development. The results suggest that education and economic growth maintain an indirect relationship that is weak against the introduction of more variables to the model and that the most significant determinants of Mexican economic growth between 1990 and 2014 were the industry value added, the technological development and the reduction of the birth rate.